Perspectives on diversity, equity, and social justice in educational leadership - Esmail, Ashraf; Pitre, Abul; Aragon, Antonette (The National Association for Multicultural Education (NAME), 2017)
Perspectives on diversity, equity, and social justice in educational leadership provides educational leaders with practical steps for implementing multicultural education into schools.